Carbon nanotube field effect transistor (CNTFET) operational transconductance amplifier (OTA) based design of high frequency memristor emulator - Khurshid, T. (John Wiley and Sons Ltd, 2021)
The design and simulation of high frequency memristor emulator using carbon nanotube field effect transistor (CNTFET) based Operational Transconductance Amplifier (OTA) has been presented out in this paper. The proposed memristor emulator design consists of two CNTFET-OTAs and one capacitor with both grounded and floating topologies available for applications. The proposed CNTFET memristor design emulator outperforms the conventional complementary metal oxide semiconductor (CMOS) based memristor emulator topologies. The performance comparison with the reported memristor emulator designs reveals that the proposed grounded and floating memristor design can work over a frequency range of 1 GHz and 10 MHz respectively in comparison to conventional CMOS based design, which works over a maximum range of 8 MHz and 0.4 MHz for grounded and floating memristor designs respectively. The proposed memristor emulator circuit also offers electronic tunability of the memristance which is important for digitally programmable application of memristors. Â© 2020 John Wiley & Sons Ltd